Investigation of the Relationship Between Nurses Psychological Capital, Job Performance, and Intention to Leave their Job - Şehrinaz Polat; Nazmiye Yıldırım; Halim İşsever (Association of Nurse Managers, 2021)
Aim: To examine the relationship between psychological capital, occupational performance, and turnover intentions. It also aims to determine the factors that predict occupational performance and turnover intention. Method: This cross-sectional study was conducted with 697 nurses working in a public university hospital between 24 May and 12 June 2019. The data were collected with an introductory information form containing the demographic and professional characteristics of the participants, the Psychological Capital Scale, the Occupational Performance Scale, and the Turnover Intent Scale. The obtained data were evaluated with Mann Whitney-U, Kruskal Wallis test, Pearson correlation, and Binary Logistic Regression analysis. Results: High hope, resilience, economic status, and self-efficacy increase nurses' performance (p≤.01). Being satisfied with the department, high resilience, working during the day, choosing the profession willingly, and high economic status decrease the turnover intention of nurses (p≤.02). Conclusion: It has been concluded that nurses' psychological capital is effective in increasing occupational performance, but it will not be sufficient in reducing turnover intentions.